2023
DOI: 10.1007/s10021-023-00822-8
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Tree-ring Width and NDVI Responses to Climate at a Landscape Level

Abstract: Inter-annual climatically driven growth variability of above-ground biomass compartments (for example, tree stems and foliage) controls the intensity of carbon sequestration into forest ecosystems. However, understanding the differences between the climatic response of stem and foliage at the landscape level is limited. In this study, we examined the climate-growth response of stem and leaf biomass and their relationship for Pinus sylvestris (PISY) and Picea abies (PCAB) in topographically complex landscapes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In addition, the NDVI values were calculated using high-resolution 30 m Landsat data to analyze and compare the climate signals of the leaf biomass and stem biomass under complex terrain. Compared with the NDVI data with a 250 m spatial resolution, the NDVI data with a 30 m spatial resolution did not enhance the correlation between the tree-ring width and NDVI, which indicates that the NDVI data with a 250 m spatial resolution may be sufficient to study the correlation between the tree-ring parameters and NDVI [66]. In addition to remote sensing observation data, phenological cameras and drones, as near-surface observation technologies, have also become new sources of vegetation data information [67].…”
Section: Research On the Relationships Between Tree-ring Parameters A...mentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the NDVI values were calculated using high-resolution 30 m Landsat data to analyze and compare the climate signals of the leaf biomass and stem biomass under complex terrain. Compared with the NDVI data with a 250 m spatial resolution, the NDVI data with a 30 m spatial resolution did not enhance the correlation between the tree-ring width and NDVI, which indicates that the NDVI data with a 250 m spatial resolution may be sufficient to study the correlation between the tree-ring parameters and NDVI [66]. In addition to remote sensing observation data, phenological cameras and drones, as near-surface observation technologies, have also become new sources of vegetation data information [67].…”
Section: Research On the Relationships Between Tree-ring Parameters A...mentioning
confidence: 90%
“…The tree-ring parameters are more closely related to climate factors than the NDVI. This might be affected by changes in biomass allocation during drought, the spectral distortion of remote sensing data, and the effects of different meteorological conditions on the stem and crown [66]. The relationship between the annual forest growth and NDVI were quantified in different forest types and regions.…”
Section: Relationships Between the Tree-ring Parameters And Vegetatio...mentioning
confidence: 99%
“…Some authors have reported weak and divergent correlations between the NDVI and tree-ring measurements of coniferous and deciduous species [38][39][40], but they used data from sensors of lower spatial resolution, which may explain this lack of significance. Mašek et al [13] reported that tree rings and the NDVI were decoupled for Pinus sylvetris and Abies picea; however, they suggested that topography is very important in explaining NDVI variation and tree growth. This is in agreement with our results, and explains why, when our data were grouped by elevation and aspect, better dendrochronological parameters could be identified.…”
Section: Tree-ring and Ndvi Correlationmentioning
confidence: 99%
“…The series of annual tree rings provide information on radial growth rates, and their correlation with vegetation indices is possible because, if the vegetation shows good vigor, it is likely that there are favorable conditions for tree growth and therefore tree rings are wider [11,12]. However, topographic variation in sites and their climatic conditions also influence the degree of correlation between rings and vegetation indices [13]. The Normalized Difference Vegetation Index (NDVI) is a well-known vegetation index that was developed by Rouse et al (1973) and that has been shown to be reliable in representing vegetation vigor variation [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative recently pursued by the scientific community is the integration of dendroecological data with remote sensing [12][13][14], assuming an interconnection between tree structures explained by the rates of increase recorded in the growth rings and vegetation indices. However, testing these connections has been challenging due to several inconsistencies that require further research [15].…”
Section: Introductionmentioning
confidence: 99%